Influence of moisture absorption on mechanical behaviour of composites - Cioffi, MOH; Voorwald, HJC; Sarton, LAJ; Zeedijk, H. B. (Netherlands Soc Materials Science, 1997)
Because of their application that normally demands high mechanical strength combined with low weight, the fibre/matrix interface became an important parameter concerning structural life. The problem of moisture absorption in materials has received attention in experimental studies on a composite systems as well as from a theorical point of view. The fibre/matrix interface plays an important role in the structural behaviour of composites due to the fact that load transfer from matrix to reinforce occurs at the interface. In this case the study of compatibility of fibre/matrix/environmental is essential to ensure a product that attend structural objectives, many times without failure possibilities. The composite used in this investigation is the carbon fibre/matrix epoxy composite, which was immersed in sea water standard during 94 days at 60 degrees C, submitted to tensile and compressive tests to study the influence of moisture absorption on mechanical behaviour. The interface was investigated through fracture surface analysis by SEM and a strong interface and a good adhesion fibre/matrix was observed.